Optimization of English Skill Improvement of Students Anuban Wangmai Sasanasart School Thailand - Adilah Fauziyah; Yani Fitriyani; Nanan Abdul Manan; Oman Hadiana; Tio Heriyana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This service activity aims to improve the English language skills of Anuban Wangmai Sasanasart School students, Thaphae District, Krabi Thailand. The target of this service activity is all students starting from Anuban (TK), Prhatom (SD) and Mattayom (SMP) Anuban Wangmai Sasanasart School. One of the community service activities carried out by the service team is the activity of one day one sentences and gymnastic an English song. The one day one sentences and gymnastic an English song activities are one of the devotional activities which are always carried out in the morning. One day one sentences is an English habituation activity in the form of one day one sentence, where there is a group of 5 students who become tutors every day to speak English which is also translated into Thai so students understand what is being said and these activities can improve students' speaking and listening skills. Furthermore, the gymnastic an English song activity is an activity that is carried out after the one day one sentences activity. Gymnastic an English song is a form of English language habituation by doing gymnastics with English songs so that students will get used to listening to English vocabulary so that students will easily remember it and with this activity students' listening skills can improve. Gymnastic an English song activity is an activity that is carried out after the one day one sentences activity. Gymnastic an English song is a form of English language habituation by doing gymnastics with English songs so that students will get used to listening to English vocabulary so that students will easily remember it and with this activity students' listening skills can improve. Gymnastic an English song activity is an activity that is carried out after the one day one sentences activity. Gymnastic an English song is a form of English language habituation by doing gymnastics with English songs so that students will get used to listening to English vocabulary so that students will easily remember it and with this activity students' listening skills can improve.